2014
DOI: 10.5117/tvt2014.3.duiz
|View full text |Cite
|
Sign up to set email alerts
|

Zoete verleiding

Abstract: Sweet Temptations: A study into the effects of a fotonovela about diabetes on low-literatesIn this experiment the effectiveness of a fotonovela for Dutch low-literates was assessed and underlying mechanisms that could account for possible persuasive effects were studied. The Entertainment Overcoming Resistance Model (EORM; Moyer-Gusé, 2008) served as a theoretical framework. The fotonovela that was used was a Dutch translation of the diabetes fotonovela ‘Sweet Temptations’ developed and tested in the US. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…In line with what Unger et al (2009) and Duizer et al (2014) found, but in contrast to the results of Koops Van’t Jagt et al (2017), we also found effects for behavioural intentions, albeit limited. Compared with the control condition, reading a fotonovela resulted in significantly higher scores on intention to exercise more regularly.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with what Unger et al (2009) and Duizer et al (2014) found, but in contrast to the results of Koops Van’t Jagt et al (2017), we also found effects for behavioural intentions, albeit limited. Compared with the control condition, reading a fotonovela resulted in significantly higher scores on intention to exercise more regularly.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding diabetes knowledge, we found that participants in both fotonovela conditions significantly performed better than participants in the control condition. These findings are similar to what Unger et al (2009), Duizer et al (2014) and Koops Van’t Jagt et al (2017) found in diabetes-related fotonovela studies performed in a first-world context.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation